2017
DOI: 10.1038/pj.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Scattering function of semi-rigid cyclic polymers analyzed in terms of worm-like rings: cyclic amylose tris(phenylcarbamate) and cyclic amylose tris(n-butylcarbamate)

Abstract: Recently reported data of the particle scattering function P(q) with the magnitude q of the scattering vector for rigid cyclic amylose tris(phenylcarbamate) (cATPC) and cyclic amylose tris(n-butylcarbamate) (cATBC) in different solvents were analyzed in terms of a novel simulation method based on the Kratky-Porod wormlike chain model. Although similar wormlike chain parameters were evaluated for both relatively flexible cyclic chains and the corresponding linear polymers, an appreciable decrease in the chain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…While P(q) of the wormlike ring cannot be calculated analytically, Tsubouchi et al [64] developed a Monte Carlo simulation method to calculate the particle scattering function Pc(q) of thin wormlike ring. Furthermore, if the chain thickness is taken into account by the touched-bead model as follows, ( ) (9) we reported that the resultant P(q) successfully reproduced the experimental data for the three amylose derivatives, that is, cATPC, cATBC, and cADMPC [24,44]. A curve fitting procedure was examined assuming log-normal molar-mass distribution with Ð = 1.05 and 1.20.…”
Section: Analyses In Terms Of the Cyclic Wormlike Chain: Catodcmentioning
confidence: 95%
See 4 more Smart Citations
“…While P(q) of the wormlike ring cannot be calculated analytically, Tsubouchi et al [64] developed a Monte Carlo simulation method to calculate the particle scattering function Pc(q) of thin wormlike ring. Furthermore, if the chain thickness is taken into account by the touched-bead model as follows, ( ) (9) we reported that the resultant P(q) successfully reproduced the experimental data for the three amylose derivatives, that is, cATPC, cATBC, and cADMPC [24,44]. A curve fitting procedure was examined assuming log-normal molar-mass distribution with Ð = 1.05 and 1.20.…”
Section: Analyses In Terms Of the Cyclic Wormlike Chain: Catodcmentioning
confidence: 95%
“…Recently, we showed that the Kuhn segment number of the ring polymer becomes larger with lowering NK for the corresponding linear chain. The current NK data are plotted along with our recent results [24,44] in Fig. 11.…”
Section: Comparison Between Catodc and Atodcmentioning
confidence: 96%
See 3 more Smart Citations